(untitled) (American International Journal of Education and Linguistics Research, 2019)
This study reveals the causes that make the EFL students poor in speaking skills. The problem was EFL students’ poor speaking skills at Kandahar University. The study used quantitative approach by developing a questionnaire consisting 15 items based on five likert scales. Two faculties were the target population of the study, and data was collected from 100 students as a random sampling which 81 were male and 19 female students. The data was analyzed and interpreted based on mean and standard deviation through SPSS software (24) version. It was revealed by the present study that different causes like, feeling shyness during presentation, nervousness when speaking with strangers even with family members, weakness of speaking when whole class pay attention, no motivation from peers and feeling fearful when speaking with lectures affect EFL students’ speaking skills.